Journal of Marine Science and Technology Official Journal of the Japan Society of Naval Architects and Ocean Engineers (JASNAOE) - Umeda, Naoya; Takagi, Ken.; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer.)
The sea is where life is said to have originated. Not only do the earth's oceans provide vital routes of transportation and a rich source of raw materials; they have also remained a challenging frontier and an essential natural habitat whose preservation will be crucial to human survival in the twenty-first century. The efforts of marine scientists and technologists are aimed at the advancement of scientific and engineering knowledge regarding the sea. The Journal of Marine Science and Technology provides a forum for the discussion of current issues in marine science and technology by publishing original, full-length, refereed contributions on research and/or developments in this field. Review papers by leading authorities are also presented. The range of topics covered in the Journal of Marine Science and Technology extends from research in the field of naval architecture, marine engineering, and ocean engineering to marine-related research in the field of environmental science and technology, oceanography, computational mechanics, and information technology. .
Keywords: Fluid mechanics; Mechanical engineering; Engineering design; Automotive engineering; Building construction; Automotive Engineering; Engineering Fluid Dynamics; Engineering Design; Offshore Engineering; Mechanical Engineering